Hubungan Perilaku Penyehatan Udara di Dalam Ruang Rumah dan gangguan Kesehatan Keluarga di kelurahan Caturtunggal Wilayah Kerja Puskesmas Depok III, Sleman, Yogykarta - Handini Citraswari; Achmad Husein; Muryoto Muryoto (Poltekkes Kemenkes Yogyakarta, 2015)
Air as one component of the environment is the most important requirement for maintaining life. Data at Depok III Community Health Centre showed that in 2013 the number of health problems due to air pollution in Caturtunggal Village was 342 cases. Behavior is a determining factor for the occurrence of family health problems. The purpose of this study was to determine the relationship between indoor air sanitation behaviors with the corresponding family health problems in the working area of the above community health centre. Method of the study was a cross sectional analytic survey with data collection instrument used was questionnaire guidance for interviewing the 210 households sample of the villagers. The data were analysed by using chi-squarestatitistical test and odds ratio at 95 % confidence level. It was found that the sanitation behavior related with risk factors for the unfulfillness condition of indoor temperature, gained a p-value of 0,112 and OR of 1,58. Meanwhile, for the other four conditions, the results were: humidity, p = 0,048 and OR = 1;771; illumination, p = 0,168 and OR = 1,533; ventilation rate, p = 0,026 and OR = 1,961, and dust, p = 0,037 and OR = 1,875. Therefore, it can be concluded that the risk factors behavior that are not significantly correlated with the corresponding family health problems are those of indoor temperature and illumination, and those that are significant are of indoor humidity, ventilation rate and dust.